ROS and Brain Gliomas: An Overview of Potential and Innovative Therapeutic Strategies - Rinaldi, Mariagrazia (Int J Mol Sci, 2016)
Reactive oxygen species (ROS) represent reactive products belonging to the partial reduction of oxygen. It has been reported that ROS are involved in different signaling pathways to control cellular stability. Under normal conditions, the correct function of redox systems leads to the prevention of cell oxidative damage. When ROS exceed the antioxidant defense system, cellular stress occurs. The cellular redox impairment is strictly related to tumorigenesis. Tumor cells, through the generation of hydrogen peroxide, tend to the alteration of cell cycle phases and, finally to cancer progression. In adults, the most common form of primary malignant brain tumors is represented by gliomas. The gliomagenesis is characterized by numerous molecular processes all characterized by an altered production of growth factor receptors. The difficulty to treat brain cancer depends on several biological mechanisms such as failure of drug delivery through the blood-brain barrier, tumor response to chemotherapy, and intrinsic resistance of tumor cells. Understanding the mechanisms of ROS action could allow the formulation of new therapeutic protocols to treat brain gliomas.